Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test. (15th August 2023) - Meng, Xiangsong; Zeng, Ping; Lin, Shangyong; Bao, Huanjun; Wu, Meirong; Yang, Lei; Jing, Gaogui; Han, Haisheng; Zhang, Chenyang; Jiang, Xiaoyun; Wang, Songlin; Ding, Wei; et al.
Abstract: In recent years, electrochemical oxidation (EO) shows the characteristics of green and high efficiency in removing chemical oxygen demand (COD) and ammonia nitrogen (NH3 –N) from wastewater, which has been favored by researchers. However, at present, most of current studies on EO remain in laboratory stage, reports about pilot-scale or even industrial tests with large treatment capacity are few, which slowing down the use of the advanced technology to practical application. In this study, bench-scale tests, pilot-scale tests (treatment capacity 200–500 L/h), and industrial tests (treatment capacity 100 m 3 /h) were carried out by EO technology in view of the characteristics of tungsten smelting wastewater (TSW) with high salinity (NaCl), COD, and NH3 –N. Results showed that the removal of COD and NH3 –N was a competitive reaction in the EO process, and COD could be removed more preferentially than NH3 –N. When NH3 –N content was low, the influent pH had a minimal effect on its removal, and when NH3 –N content was high, increasing the influent pH was beneficial to its removal. Industrial tests showed that the one-step removal of COD and NH3 –N in TSW met the standard, and the power consumption per cubic meter of wastewater was only 4.2 kW h, and the treatment cost was much lower than the two-step process of "breaking point chlorination to remove NH3 –N and adding oxidant to remove COD". This study has successfully realized industrial application of EO technology in TSW treatment for the first time and provided a successful case, which is helpful to accelerate the popularization and application of this technology in the field of high salinity organic ammonia nitrogen wastewater treatment. Highlights: One-step removal of COD and NH3 –N from high salinity TSW was achieved by EO. The removal of COD and NH3 –N was a competitive reaction in the EO process. COD could be preferentially removed over NH3 –N. The EO is the first time to realize industrial application in TSW treatment. The EO is very suitable for popularization in high salinity industrial wastewater.